1996
DOI: 10.1177/00220345960750030301
|View full text |Cite
|
Sign up to set email alerts
|

Does an Incremental Filling Technique Reduce Polymerization Shrinkage Stresses?

Abstract: It is widely accepted that volumetric contraction and solidification during the polymerization process of restorative composites in combination with bonding to the hard tissue result in stress transfer and inward deformation of the cavity walls of the restored tooth. Deformation of the walls decreases the size of the cavity during the filling process. This fact has a profound influence on the assumption--raised and discussed in this paper--that an incremental filling technique reduces the stress effect of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
190
0
32

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(226 citation statements)
references
References 15 publications
4
190
0
32
Order By: Relevance
“…Moreover, mathematical analysis of the stresses generated by polymerization suggested that there are problems associated with incremental filling techniques, such as higher tensile stress concentrations at the restoration-enamel interface than those found with single-increment fillings [65].…”
Section: The Effect Of Placement Techniquesmentioning
confidence: 99%
“…Moreover, mathematical analysis of the stresses generated by polymerization suggested that there are problems associated with incremental filling techniques, such as higher tensile stress concentrations at the restoration-enamel interface than those found with single-increment fillings [65].…”
Section: The Effect Of Placement Techniquesmentioning
confidence: 99%
“…10,41 A popular approach is to restore a cavity in oblique increments to avoid bonding to opposite walls. This technique has been suggested to result in less cuspal flexure compared to a single increment based on tests carried out with aluminum blocks.…”
Section: Finite Element Analysis (Fea)mentioning
confidence: 99%
“…Actually, placing composite in oblique increments causes stresses that can be even higher than would be obtained with a single increment fill (bulk filling). 8,9,41 It is important to emphasize that regardless of the shrinkage stress, proper polymerization throughout a conventional composite depth is difficult to obtain when the material is light cured in a single increment. 8 Reducing the conversion of composite would likely result in reduced stress due to lower volumetric shrinkage, but comes at the expense of the material properties.…”
Section: Finite Element Analysis (Fea)mentioning
confidence: 99%
“…The preparation was refined and modified for composite restorations where there were rounded internal line angles, and a beveled cavosurface was employed to expose the maximum amount of enamel rods for bond strength. 2 A combination of the incremental [3][4][5][6][7][8][9][10][11][12] and stratified layering technique 5 was used to fill the tooth. In the incremental technique, each layer was placed in a wedge formation no more than 2-mm thick.…”
Section: Techniquementioning
confidence: 99%